2017
DOI: 10.1111/ene.13509
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic features of patients with facial‐sparing facioscapulohumeral muscular dystrophy

Abstract: Facial-sparing scapular myopathy is characterized as mild myopathic symptoms and chronic progression of weakness. The diagnosis should be accurately confirmed through FSHD-sized fragment detection and 4qA/B variant determination. Although the next generations of SHD had more severe muscular symptoms, local hypomethylation within D4Z4 was not found as a modifier for clinical heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
5
19
1
Order By: Relevance
“…When we consider that involvement of facial muscles in FSHD may be mild and asymptomatic, the percentage of group 2 patients could be slightly overestimated because of the self‐reported nature of the clinical findings. Nevertheless, results of our investigations in the UK FSHD registry support the notion of a different disease course in these 2 clinical subgroups, as has been recently reported in a Chinese cohort …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When we consider that involvement of facial muscles in FSHD may be mild and asymptomatic, the percentage of group 2 patients could be slightly overestimated because of the self‐reported nature of the clinical findings. Nevertheless, results of our investigations in the UK FSHD registry support the notion of a different disease course in these 2 clinical subgroups, as has been recently reported in a Chinese cohort …”
Section: Discussionsupporting
confidence: 90%
“…This phenotype, also defined as facial‐sparing scapular myopathy , is often detected in clinical practice among carriers of D4Z4‐reduced alleles and should be distinguished from other forms of myopathies, including “scapuloperoneal syndromes.” Data from the Italian National Registry for FSHD (G. Ricci, R. Tupler: original data) suggest that the incomplete FSHD phenotype (B1) may be associated with a milder motor disability and slower progression of weakness compared with the classical FSHD phenotype (category A). Similar findings were reported by He and coworkers in a cohort of Chinese patients with FSHD.…”
supporting
confidence: 91%
“…This observation challenges the concept of facial-sparing FSHD. [23][24][25][26][27] Mild facial muscle weakness is likely to remain unnoticed both by the patient and the physician. 2 Subtle weakness of the orbicularis oculi muscles leads to a "signe de cils"-an inability to bury the eyelashes completely when attempting to close the eyes tightly.…”
Section: Discussionmentioning
confidence: 99%
“…It was notable that 11 of 35 (31%) mosaic individuals presented a clinical spectrum typical of non-mosaic FSHD (category A based on CCEF), raising the possibility that previously unrecognised mosaicism can perhaps explain previously reported yet genetically indeterminate clinical presentations in patients with FSHD, an idea bolstered by previous suggestions that somatic mosaic FSHD often goes undetected 12. Further, our observation that 5 (14%) mosaic individuals presented non-typical phenotypes without facial weakness suggests a possible genetic explanation—again, underdiagnosed mosaicism—to potentially explain previously reported cases of the facial-sparing scapular myopathy FSHD subtype 26. The non-penetrance frequency of about 50% (18 of 35) in our study was substantially higher than the 17% (12 of 69)27 reported in the latest study of non-mosaic FSHD (χ 2 =11.23, p=0.001), a comparison which supports previous studies indicating that mosaic FSHD has higher clinical tolerance yet slighter disease severity than non-mosaic FSHD.…”
Section: Discussionmentioning
confidence: 55%